Meta-analysis of the effect of road work zones on crash occurrence. (November 2017) - Theofilatos, Athanasios; Ziakopoulos, Apostolos; Papadimitriou, Eleonora; Yannis, George; Diamandouros, Konstantinos
Highlights: The impact of workzone duration and length on crashes was examined. Three meta-analyses and two meta-regression analyses were conducted. Results show regression coefficients of 0.1703 for duration and 0.862 for length. Those results are significant when workzone length is examined. Study year, region and model specification were found to affect overall estimates. Abstract: There is strong evidence that work zones pose increased risk of crashes and injuries. The two most common risk factors associated with increased crash frequencies are work zone duration and length. However, relevant research on the topic is relatively limited. For that reason, this paper presents formal meta-analyses of studies that have estimated the relationship between the number of crashes and work zone duration and length, in order to provide overall estimates of those effects on crash frequencies. All studies presented in this paper are crash prediction models with similar specifications. According to the meta-analyses and after correcting for publication bias when it was considered appropriate, the summary estimates of regression coefficients were found to be 0.1703 for duration and 0.862 for length. These effects were significant for length but not for duration. However, the overall estimate of duration was significant before correcting for publication bias. Separate meta-analyses on the studies examining both duration and length was also carried out in order to have rough estimates of the combined effects. The estimate of duration was found to be 0.953, while for length was 0.847. Similar to previous meta-analyses the effect of duration after correcting for publication bias is not significant, while the effect of length was significant at a 95% level. Meta-regression findings indicate that the main factors influencing the overall estimates of the beta coefficients are study year and region for duration and study year and model specification for length.